PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) BERBANTUAN MEDIA VIDEO TERHADAP HASIL BELAJAR IPA DI SMP NEGERI 2 KANATANG - Saingo, Lidia -; Bano, Vidriana Oktoviana; Ndjoeroemana, Yohana (P2M STKIP Siliwangi, 2023)
This study aims to determine the effect of the cooperative learning model of the think pair share type assisted by video media on student learning outcomes in the human digestive system class VIII SMP Negeri 2 Kanatang. This type of research is a quasi-experimental. In this case the study chose a nonequivalent control group. The sample design in this study was 26 students of class VIIIC as the control class and 26 students in class VIIIB as the experimental class. The sampling technique. This research was conducted at SMPN 2 Kanatang, even semester, Academic year 2021/2022. The research instrument was a written test consisting of 15 pretest questions and 20 posttest questions in the form of multiple choices. The research data were analyzed using statistical tests, namely validity and reliability tests, normality, homogeneity tests, and ti tests (paired sample t tests) using SPSS version 22. Based on the results of the analysis, the average posttest scores of the experimental class students were obtained.  with the cooperative learning model of the think pau share type assisted by video media is 79.73 higher than the class taught using lectures of 68.58.  The results of testing the hypothesis with the parted sample t test obtained sig (2-tailed) <0,05 (0.000 0,05).  This shows that there is a diversion of the cooperative learning model of the think pair share type assisted by video media to student learning outcomes in class VIII human digestive system material at SMP N 2 Kanatang.